2004
DOI: 10.1093/jxb/erh205
|View full text |Cite
|
Sign up to set email alerts
|

Do iron plaque and genotypes affect arsenate uptake and translocation by rice seedlings (Oryza sativa L.) grown in solution culture?

Abstract: The effects of Fe concentrations in the pretreatment solution on the induction of plaque and the differences between genotypes on arsenate uptake by and translocation within rice seedlings grown in nutrient solution in the greenhouse were investigated. After iron plaque on rice roots was induced in solutions containing 20, 40, 60, 80, and 100 mg Fe2+ l(-1), seedlings were transplanted into nutrient solution with 0.5 mg As l(-1). The formation of iron plaque was clearly visible as a reddish coating on the root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
141
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(154 citation statements)
references
References 32 publications
13
141
0
Order By: Relevance
“…This finding is in agreement with the findings by Liu et al [19], Rahman et al [9] and Bhattacharya et al [8]. According to Liu et al [20] the iron oxides or iron plaques formed around root of the rice plant are responsible for the arsenic binding in root. The resultant is the reduction of translocation of arsenic from root to straw, husk, and grain portions of the rice plant.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in agreement with the findings by Liu et al [19], Rahman et al [9] and Bhattacharya et al [8]. According to Liu et al [20] the iron oxides or iron plaques formed around root of the rice plant are responsible for the arsenic binding in root. The resultant is the reduction of translocation of arsenic from root to straw, husk, and grain portions of the rice plant.…”
Section: Resultssupporting
confidence: 92%
“…The results indicated an appreciable low efficiency (TF = 0.08−0.19) in translocation of arsenic from root to shoot whereas TF values were found to be much higher from shoot to grain (TF = 0.11−0.46) for almost all the analyzed rice varieties. The lower TF values for translocation of arsenic from root to shoot revealed the strong capability of root tissues to hold the arsenic, which was related with the presence of iron plaques [20]. Other than the White Minikit variety, translocation of arsenic from straw to grain (TF = 0.25−0.46) by all other HYVs was evaluated to be much higher than those by the studied local and hybrid rice varieties.…”
Section: Resultsmentioning
confidence: 82%
“…due to the formation of iron plaques, as reported in a previous study and with synchrony with the present work ). It has also been reported that the accumulation of arsenic in rice plants is highest in the root zones and decrease significantly in the upper parts of the plant (Liu et al 2004). This was verified by the results of the present study, which showed a root > basal stem > median stem > apical stem>leaves>grains trend of arsenic accumulation in O. sativa.…”
Section: Resultsmentioning
confidence: 92%
“…Arsenic speciation was separated by a PRP-X100 anion exchange HPLC column (150×4.1 mm, Hamilton, Netherlands) under the solution of 7.0 mmol L −1 (NH 4 ) 2 HPO 4 and 7.0 mmol L −1 NH 4 NO 3 (pH=6.2). Roots were incubated in DCB (dithionite-citrate-bicarbonate) solution for the extraction of iron plaques on the root surface (Taylor and Crowder 1983;Liu et al 2004). Arsenic concentration in the iron plaque extraction solution was determined by ICP-MS (Agilent 7500, Agilent Technologies, USA).…”
Section: Determination Of Fe 2+ S 2− and As Concentrationsmentioning
confidence: 99%